Evaluation of employee brand using typological analysis in Indian airline organisation. (2018) - Thamaraiselvan, N.; Sridevi, P.; Arasu, B. Senthil; Srinivasan, Thushara
A favourable employee brand gives service organisations competitive advantage. We analyse the typology of employee branding in an Indian airline company using finite mixture partial least squares (FIMIX-PLS). The employees of an airline organisation, Chennai division, run by the Government of India were surveyed and the types of employee brands prevalent in the organisation were identified. The empirical analysis substantiates the typology by observing the presence of four types in employees namely, all-stars, injured reserves, rookies and strike-out kings. The employees in all-star category have high knowledge of the desired brand (KDB) and perceive that the psychological contract (PC) has been upheld. The KDB of 'injured reserves' employees are high whereas they perceive violation of PC. The 'rookies' employees' KDB is low while their PC is favourable. Both the KDB and PC of 'strike-out kings' are low. The result also uncovers 'department', using chi-squared automatic interaction detection (CHAID), as a categorical variable that explains the segmentation. The management should enhance brand-centric human resource practices to make the organisation an 'all-star'.